SOSIALISASI HERBAL KUNYIT SEBAGAI ANTIMIKROBA PADA SANTRIWATI DI PONDOK PESANTREN HIDAYATULLOH AL MUHAJIRIN BANGKALAN - Renny Novi Puspitasari (STIKES NGUDIA HUSADA MADURA, 2022)
Pondok pesantren is a gathering place for many people where it is susceptible to disease transmission. Staphylococcus aureus is a normal flora in humans, but in high amounts it can cause mild to systemic skin infections. Turmeric is a plant containing curcumin grown in Indonesia, used as a spice in cooking and medicine. Curcumin has antibacterial activity of Gram negative and Gram positive by denaturing and damaging cell membranes so that it interferes with metabolic processes.The problem faced is the lack of knowledge about the benefits of turmeric as an antimicrobial at Hidayatullah Al Muhajirin Islamic Boarding School, the solution to the problem is to provide socialization of the benefits of turmeric as an antimicrobial. The method used is lecture and discussion. The purpose of providing information about the benefits of turmeric as an anti-microbial. The implication of the activity is an increase in the knowledge of santriwati, with the average score of the pretest and posttest being 50.67 and 78.00. The presentation proved to provide additional benefits of knowledge about the benefits of turmeric as an anti-microbial for santriwati at Pondok Pesantren Hidayatulloh Al Muhajirin Bangkalan.